1998
DOI: 10.1007/s11664-998-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

The microstructures of the Sn-Zn-Al solder alloys

Abstract: The microstructures of the Sn-Zn-Al lead-free solders have been investigated using scanning electron microscopy. The Al and Zn contents of the solders investigated were 0.45%~4.5% and 8.55%~85.5%, respectively. The solders were prepared from the Zn-5Al master alloy and Sn. The precipitates formed in these solders were analyzed for their compositions with energy dispersive spectroscopy. The eutectic temperature and the transition temperatures of these solders upon cooling were identified with cooling curves as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 17 publications
4
30
0
Order By: Relevance
“…The bright-gray area and dark-gray area in Figure 1 denotes the primary β-Sn phase and eutectic (Sn + Zn) networks, respectively. This result is consistent with binary-phase diagram of Sn-Zn, which shows a typical binary-eutectic phase diagram with no intermetallic compounds and limited solubility of the two elements in each phase [9]. Much coarser primary β-Sn grains can be found only in the Sn-9.0Zn-0.5Al (SZA905) alloy as shown in Figure 1 [23], which offers preferred sites for nucleation, resulting in grain refining and uniform microstructure as reported in our previous work [3].…”
Section: As-solidified Microstructuresupporting
confidence: 89%
See 1 more Smart Citation
“…The bright-gray area and dark-gray area in Figure 1 denotes the primary β-Sn phase and eutectic (Sn + Zn) networks, respectively. This result is consistent with binary-phase diagram of Sn-Zn, which shows a typical binary-eutectic phase diagram with no intermetallic compounds and limited solubility of the two elements in each phase [9]. Much coarser primary β-Sn grains can be found only in the Sn-9.0Zn-0.5Al (SZA905) alloy as shown in Figure 1 [23], which offers preferred sites for nucleation, resulting in grain refining and uniform microstructure as reported in our previous work [3].…”
Section: As-solidified Microstructuresupporting
confidence: 89%
“…For example, the third element suggesting adding to Sn-9Zn eutectic alloy are Ag [4] [5], Bi [6] [7], In [8], Al [9] [10] and Ce/La [11] [12]. For instance, McCormack and Jin [8] found that small additions of 5% In can improve the ductility of Sn-Zn base solders.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Ternary alloys include Sn-Ag-Zn, 15 Sn-ZnIn, 16,17 Sn-Ag-Sb, 18 Bi-Sb-Sn, 19 Sn-Bi-Ag, 20 Sn-Ag-Cu, 21 and Sn-Zn-Al. 22 It is seen that all the reported solders are Sn-rich alloys. Sn, however, reacts easily with the substrate materials such as Cu to form a solid solution or intermetallic compound.…”
Section: Introductionmentioning
confidence: 95%
“…The Sn-Zn-Al solder system exhibits an eutectic temperature of around 199.7∞C. 22 Al is expected to improve the high temperature oxidation resistance of the solder, 25 but not the corrosion resistance. 26 Al also forms a solid solution with Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental studies of the ternary phase diagrams of the Al-Sn-Zn systems have been already reported [26,27]. The microstructure of the systems was experimentally determined by Lin et al [28]. In addition, the oxidation resistance of 91Sn-8.55Zn-0.45Al (wt.%) alongside that of other systems have been measured [29], and a detailed assessment of the system has also been given by Fries et al [30].…”
Section: Introductionmentioning
confidence: 99%